Upaya Meningkatkan Hasil Belajar Matematika Menggunakan Metode Discovery Learning pada Siswa Kelas VI SDN 14 Koto Baru Kabupaten Dharmasraya Semester Genap Tahun Pelajaran 2020/2021: Efforts to Improve Mathematics Learning Outcomes Using the Discovery Learning Method for Class VI Students of SDN 14 Koto Baru, Dharmasraya District, Even Semesters for the 2020/2021 Academic Year - neng aini (International Journal of Technology Vocational Education and Training, 2022)
In the world of education, the model and application of methods are still not well applied. T This research is a classroom action research (PTK) that aims to perform actions of improvement, improvement and change for the better. In this study, which is used as the subject of research is all students of class VI SDN 14 Koto Baru Koto Baru District Dharmasraya Regency with a total of 33 students, namely 13 men and 20 women. Implementation time in the Even semester of the 2020/2021 academic year from January to April 2021 with class actions divided into 2 cycles. The results of the study obtained that the value of the learning outcomes of students who completed learning before the cycle as many as 4 students (12.12%), who completed in cycle I as many as 14 students (63.64%) while in cycle II as many as 27 students (81.82%) and can be concluded that using Discovery Learning strategy can improve student learning outcomes in the subject of Mathematics Build space. In addition, students enjoyed learning the percentage of student observations that had been discussed previously. Learning Mathematics while playing, this strategy also educates students to be more competitive in the classroom with the application of this strategy also provides many interesting experiences for students.